Neutron reflectivity and soft condensed matter - Penfold, J (2002)
During the last 10-15 years neutron reflectivity has emerged as a powerful and important technique for the study of surfaces and interfaces. The selectivity and sensitivity afforded by deuterium/hydrogen exchange makes the technique particularly attractive for application to the broad field of colloid and interface science. The development of the instrumentation, specialised sample environment equipment and analysis techniques has resulted its application to complex interfaces and environments and in the study of complex multi-component systems. This review provides a summary of those developments in the last two years. © 2002 Elsevier Science Ltd. All rights reserved.